A new species of Billolivia (Gesneriaceae) from Central Vietnam - Lý, Ngọc-Sâm (Phytotaxa, 2017)
Billolivia middletonii, a new species from Cà Ðam Mountains, Quảng Ngãi Province, Central Vietnam, is described and illustrated. A morphological description, a colour plate, the distribution, ecological information, the conservation status, and notes to species of Billlolivia in Vietnam are given.